Recurrent high creatine kinase levels under clozapine treatment - a case report assessing a suspected adverse drug reaction - Wiss, Florine M.; Allemann, Samuel S.; Meyer zu Schwabedissen, Henriette E.; Stäuble, Céline K.; Mikoteit, Thorsten; Lampert, Markus L. (Frontiers in Psychiatry, 2024)
Suspected adverse drug reactions (ADRs) during treatment with clozapine often prompt therapeutic drug monitoring (TDM) in clinical practice. Currently, there is no official recommendation for pharmacogenetic (PGx) testing in the context of clozapine therapy. In this case report, we demonstrate and discuss the challenges of interpreting PGx and TDM results highlighting the possibilities and limitations of both analytical methods. A 36-year-old male patient with catatonic schizophrenia was treated with clozapine. He experienced multiple hospitalizations due to elevated creatine kinase (CK) levels (up to 9000 U/L, reference range: 30-200 U/L). With no other medical explanation found, physicians suspected clozapine-induced ADRs. However, plasma levels of clozapine were consistently low or subtherapeutic upon admission, prompting us to conduct a PGx analysis and retrospectively review the patient’s TDM data, progress notes, and discharge reports. We investigated two possible hypotheses to explain the symptoms despite low clozapine plasma levels: Hypothesis i. suggested the formation and accumulation of a reactive intermediate metabolite due to increased activity in cytochrome P450 3A5 and reduced activity in glutathione S-transferases 1, leading to myotoxicity. Hypothesis ii. proposed under-treatment with clozapine, resulting in ineffective clozapine levels, leading to a rebound effect with increased catatonic symptoms and CK levels. After considering both data sources (PGx and TDM), hypothesis ii. appeared more plausible. By comprehensively assessing all available TDM measurements and examining them in temporal correlation with the drug dose and clinical symptoms, we observed that CK levels normalized when clozapine plasma levels were raised to the therapeutic range. This was achieved through hospitalization and closely monitored clozapine intake. Therefore, we concluded that the symptoms were not an ADR due to altered clozapine metabolism but rather the result of under-treatment. Interpreting TDM and PGx results requires caution. Relying solely on isolated PGx or single TDM values can result in misinterpretation of drug reactions. We recommend considering the comprehensive patient history, including treatment, dosages, laboratory values, clinic visits, and medication adherence.